ESG Disclosure dan Dewan Komisaris Independen terhadap Nilai Perusahaan dengan Kualitas Audit sebagai Variabel Moderasi - Hasna Shafira; Christina Dwi Astuti (IPM2KPE, 2024)
This research aims to evaluate the impact of environmental disclosure, social disclosure, governance disclosure, and the existence of an independent board of commissioners on company value, by considering the role of audit quality as a moderating variable. The research method used is a quantitative causality approach using secondary data. The research results show that environmental disclosure, social disclosure and governance disclosure have a positive influence on company value. However, no significant influence was found from the existence of an independent board of commissioners on company value in the context of this research. In addition, audit quality is proven to strengthen the influence of environmental disclosure on firm value, but does not strengthen the influence of social disclosure and governance disclosure on firm value. The conclusion is that corporate transparency and accountability have a significant role in determining company value. Keywords: Independent Board of Commissioners, Environmental Disclosure, Governance Disclosure, Audit Quality, Company Value, Social Disclosure